Interview with Carol Pullen, Oro Agri. (1st August 2022) - Blake, Robin; Pullen, Carol
The company was started over twenty years ago by Erroll Pullen in South Africa. He started experimenting with orange oil and worked with Stellenbosch University to test it and after confirming that it had both fungicidal and insecticidal properties, which was unusual and therefore uniquely patentable, the company was started and its first product PREVAM was born. Another office was opened in the USA and then Europe, and it is now present in over 85 countries, with a physical presence in over 40. It has factories in the EU, US, Brazil and South Africa and supply globally. Four years ago the company was sold to a South African company Omnia Holdings who then sold it Rovensa Group, who are the current owners with one of the largest footprints in the biosolutions market, seeing the purchase of Oro Agri as an opportunity to broaden their portfolio and international footprint. With a vision of offering differentiated biocontrol solutions not only to the organic market, but especially to facilitate biological synergies with traditional crop protection products targeting more sustainable solutions, the OroBio-Pheno Science and Innovation Center, complete with indoor and outdoor phenotype system, is currently under construction and will provide development services to all the Oro Agri and ROVENSA group companies.